A Post-Crisis Reality and Banks’ Operation as Well as Behavior of their Employees from the Ethical Point of View - Świeszczak, Krzysztof; Świeszczak, Marika (Journal of Finance and Financial Law, 2016)
Crises which have appeared in recent years have been the major determinant of the functioning of the banking sector, but now the main task of the bank as an institution of public trust is to design activities so that banks could avoid the negative consequences of possible future turmoils. The key role play their employees, especially those working with clients, because in the face of a crisis of confidence, rebuilding the credibility and positive image can be the foundation of competitiveness of banks. The aim of the article is to analyze the condition of the banking sector from the perspective of the global financial crisis and a crisis of confidence, an overview of the activities in the field of ethics undertaken by banks after the crisis and assessment of their effectiveness on the basis of employees opinions.